Analysis Of Bamboo Soil Nailing Using Finite Element Method - Nurdayana Ramli (School of Environmental Engineering, Universiti Malaysia Perlis, 2016)
To study the effectiveness of bamboo as a replacement of steel rebar in soil nailing using FEM. To study the effect of groundwater table using bamboo in soil nailing system.